2022
DOI: 10.53771/ijstra.2022.2.1.0023
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Acute Toxicity of Aqueous Extracts of Tephrosia vogelii and Albizia gummifera on Clarias gariepinus (African Catfish) Fingerlings

Abstract: Fishing with Albizia gummifera is gaining more popularity than Tephrosia vogelii by local fishermen of Mangu Local Government Area, Plateau State and other parts of Nigeria, because of its productiveness and availability. Acute toxicity of aqueous extracts of leaf and bark of T. vogelii and A. gummifera were conducted on C. gariepinus fingerlings in static non-renewable bioassay. Dissolved Oxygen (DO) mg/L, pH and Temperature (°C) were monitored daily throughout the period by using ExStik® DO600 meter. Definit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Although biodegradable phytochemicals of many plant extracts are safe for human consumption, most are traditionally used as fish poison [3]. Studies have shown that plant extracts (Tephrosia vogelii [4], Balanites aegyptiaca [5], and Albizia gummifera [6]) safe for human consumption [7] have phytochemicals that are noxious to fish. In Nigeria, common plants used as fish poison include Tephrosia candida, Datura innoxia, Psychotria microphylla, and B. aegyptiaca [3,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Although biodegradable phytochemicals of many plant extracts are safe for human consumption, most are traditionally used as fish poison [3]. Studies have shown that plant extracts (Tephrosia vogelii [4], Balanites aegyptiaca [5], and Albizia gummifera [6]) safe for human consumption [7] have phytochemicals that are noxious to fish. In Nigeria, common plants used as fish poison include Tephrosia candida, Datura innoxia, Psychotria microphylla, and B. aegyptiaca [3,8,9,10].…”
Section: Introductionmentioning
confidence: 99%